The intrigue of ethics : a reading of the idea of discourse in the thought of Emmanuel Lévinas - Dudiak, Jeffrey (Perspectives in continental philosophy ;, 2001)
"The Intrigue of Ethics' explains how human beings can live more peacefully with one another by understanding the conditions of possibility for dialogue. The arguments to this point are taken largely from Emmanuel Levinas's 'Totality and Infinity' and his 'Otherwise than Being."